Seni Persuasif dalam Podcast: Kajian Sintaksis - Rintan Amalia Rohar; Fitri Amilia; Hasan Suaedi (LPPM Institut Pendidikan Nusantara Global, 2026)
This study discusses the persuasive art in the preaching utterances of Habib Husein Ja’far Al-Hadar on Deddy Corbuzier’s YouTube channel, particularly in the Log-in Season Episode, through a syntactic analysis based on Austin and Searle’s speech act theory. The purpose of this research is to describe the types of sentences used by Habib Ja’far in delivering persuasive messages an to explain the accompanying illocutionary function. The method used is qualitative with observastion and note taking techniques, in which verbal utterances are classified according to sentence types (declarative, imperative, prohibitive, and interrogative) and analyzed in relation to their pragmatic functions. The results of the study show that Habib Ja’far employs various syntactic structures to create strong persuasive effects. Declarative sentences are used to instill moral and spiritual values, imperative and prohibitive sentences serve to guide the audience’s behavior, while interroative sentences function to evoke the listener’s awareness through reflection. The combination of sentencesstructure and illocutinary meaning forms a preaching style that is gentle, logical, and emotional, making religious messages more easily accepted by diverse audience.